Morphometric Evaluation of Dry Humerus Bone in a Medical College of Eastern Nepal - Chaudhary, Raju Kumar; Dhakal, Arun; Sah, Sanjib Kumar; Prajuli, Surya B; Pokhrel, Suman; Deo, Santosh Kumar (Birat Journal of Health Sciences, 2019)
Introduction: Anthropometric measurement of dry bones are helpful to estimate the stature. It is useful for differentiating unidentified bodies, skeletal remains, surgical procedures and are helpful for anthropologists, anatomists, forensic and surgery. Objective: The objective of this study was to find the morphometric measurements of dry Humerus bone available at Birat Medical College and Teaching Hospital of Eastern Nepal. Methodology: A cross- sectional study was conducted from 28th June- 28th July 2019 in the department of Anatomy of Birat Medical College and Teaching Hospital by taking 59 dry humerus bone. Various parameters such as maximum length, circumference of surgical neck, epicondylar breadth together with position and number of nutrient foramina were measured. Data was collected using osteometric board, vernier caliper and tape. The number, direction and location of nutrient foramina were observed macroscopically by using a fine wire. Ethical clearance was taken from Institutional Review Committee of Birat Medical College and Teaching Hospital. Results: Among 59 dry humerus bone, majority (32) were left humerus. No statistical significant difference was found in morphometric measurements between right and left side of dry Humerus bone. The single nutrient foramen was present in 85.18% and 81.25% of right and left humeri respectively. Double nutrient foramina in 14.81% of right humeri and 15.62% of left humeri. Triple nutrient foramina was only seen in left humeri (3.12%). Conclusion: Single nutrient foramen is most common in both sides of humeri. No statistical significant difference was found between right and left humeri in the different parameters such as maximum humeral length (MHL), vertical diameter of superior articular surface (VDSAS), circumference of surgical neck (CSN), circumferences of middle shaft (CMS), epicondylar breath (EB), medial epicondyle to capitulum (ME - C), transverse diameter inferior articular surface (TDIAS), maximum transverse diameter of trochlea (MTDT), anteroposterior diameter of the trochlea (APDT) and position of nutrient foramina (PNF).